Using Reactivity Predictors for Enhancing the Electrocatalytic Activity of mn4 Molecular Catalysts for the Oxygen Reduction Reaction: The Role of the N-Pyridinium Functional Group in the Porphyrazine-Derivative Ligands - Zagal-Moya, J; Zagal-Moya, J; Ponce-Hormazabal, I; Muñoz-Moena, L; Muñoz-Moena, L; Scarpetta-Pizo, L; Scarpetta-Pizo, L; Venegas-Toledo, R; Onate, R (Elsevier Ltd, 2023)
Using reactivity predictors to enhance or control the electrocatalytic activity of materials is a fascinating concept. This is especially true for the development of alternative platinum metal group-free materials as it facilitates the rational design of active catalytic materials for the oxygen reduction reaction (ORR). In previous work, we have found that the peripheral and non-peripheral electron-withdrawing effects and the electron-pull effect from axial extraplanar ligand in iron-phthalocyanine (FePc) are key factors in improving the binding energy between the active Fe site and O2 resulting in an increase of the electrocatalytic activity of FePcs for the ORR. In this work, we have utilized fundamental principles of electrocatalysis and DFT calculations to design and synthesize FeN4 molecular catalysts to increase their catalytic performance for the ORR through the "pull" effect. To achieve this, by chemical synthesis, we have incorporated pyridinium functional groups (N+py) in peripheral and non-peripheral positions into the porphyrazine cyclic ligands. In this fashion we obtain the porphyrazinium molecular catalysts, [Fe(II)2,3-(TMe)TPyPz]4+ and [Fe(II)3,4-(TMe)TPyPz]4+. Because these new compounds are not commercially available and, to the best of our knowledge, they have not been tested for ORR. In order to determine their effectiveness, we have compared porphyrazinium with neutral analog porphyrazine compounds (Fe(II)TPyPz) and perfluorinated and perchlorinated iron phthalocyanines, which are currently the best molecular catalysts for ORR. The electrocatalytic activity was determined for each molecular catalyst deposited on the edge plane of a graphite electrode (EPG) surface in an alkaline medium. Only for the purpose of comparison we include two Fe porphyrins studied previously, which show low activity for ORR. Although the DFT theoretical analysis of porphyrazinium complexes suggests a high activity for these catalysts, our experimental findings revealed the opposite trend. Therefore, this finding makes us reconsider the interfacial effects, such as the counter-ions effects on N+py that could influence the electron-pull effect, opening new insights for designing molecular catalysts considering interface engineering. Moreover we report for the first time, the reactivity linear relationship between the metal-centered redox potential gap (E°Fe(III)/(II) – E°Fe(II)/(I))) with the electrocatalytic activity for ORR for all catalysts studied, emerging this potential gap as a possible and promising new reactivity descriptor for ORR in MN4 catalyst. © 2023